Large-scale climatic controls on Lake Baikal ice cover - Todd, MC; Mackay, AW (AMER METEOROLOGICAL SOC, 2003)
Long-term records of winter ice duration, formation, and breakup dates ( 1869 - 1996) and maximum thickness ( 1950 - 95) on Lake Baikal are analyzed to determine the nature of temporal trends and the relationship with the large-scale atmospheric circulation. There are highly significant trends of decreasing ice duration ( and thickness) over the period, associated with later ice formation and earlier breakup dates. These trends are broadly in line with those of winter air temperatures in the region. Variability in Lake Baikal ice formation date, duration, and thickness is significantly related to winter temperatures over a wide area from the Caspian Sea to the Pacific and from northern India to the Kara Sea off the northern coast of Siberia. Thus, Lake Baikal ice cover is a robust indicator of continental-scale winter climate. Correlation and composite analysis of surface and upperatmospheric fields reveal that interannual variability in ice cover is associated with a tripolar pattern of upper-level geopotential height anomalies. In years of high ( low) ice duration and thickness, significant positive (negative) 700-hPa geopotential height anomalies occur over northern Siberia and the Arctic, complemented by negative (positive) anomalies over central-eastern Asia and southern Europe. This structure induces an anomalous meridional flow regime in eastern Siberia with cold ( warm) temperature advection from the northeast ( southwest) in years of high ( low) ice duration and thickness. Analysis of the lower-tropospheric heat budget during years of extreme early and late ice onset indicates that horizontal temperature advection is largely responsible for the observed temperature anomalies. These circulation anomalies are associated with certain recognized patterns of Northern Hemisphere climate variability, notably the Scandinavian and Arctic Oscillation patterns. Significant correlations also occur between Lake Baikal ice cover and the Pacific - North American pattern in the previous winter. The component of variability in Lake Baikal ice cover unrelated to these modes of Northern Hemisphere climate variability is associated with the position and intensity of the Siberian high.